Christmas card from G. Trömel to Georg Bredig - Trömel, G.
A Christmas card featuring a line drawing of the Town Hall of Old Town Dusseldorf, Germany.
Keywords: Bredig, Georg, 1868-1944; Trömel, G.; Christmas cards